Effect of Brand Image, Price, and Quality of Product on The Smartphone Purchase Decision - Hadi Arjuna; Sarah Ilmi (EkBis: Jurnal Ekonomi dan Bisnis, 2019)
One of the competing mobile brands in Indonesia is xiaomi, the xiaomi brand itself began to be known by the people of Indonesia since 2013 and successfully exploded in the market in 2014 by creating their flagship product, smartphone. Various findings of a good product quality will affect the brand image of a product, brand image describes the results of the views or perceptions of consumers towards a particular brand, which is based on comparison and consideration with several other brands, on the same type of product. This research aims is to find out whether there is a significant influence between product quality, brand image, and price on smartphone purchase decision. This research uses a multiple regression approach and 100 respondent in Yogyakarta provincy, the results of the research output show that all hypotheses tested show achievement in accordance with the research parameters.